Farmers’ preferences for maize attributes in eastern and Western Uganda - Ajambo, R.; Elepu, G.; Bashaasha, B.; Okori, P. (African Journals Online (AJOL), 2017)
Maize (Zea mays L.) is an important staple food crop in Uganda and is emerging as a cash crop for smallholder farmers. Maize has, therefore, been prioritised by the Government of Uganda for continuous improvement through the national agricultural research system, resulting in the release of several improved varieties. However, adoption rates of the improved varieties among farmers remains low possibly due to non-inclusion of important non-yield productive and consumptive attributes in the new maize varieties. This study was conducted to identify and economically evaluate non-yield productive and consumptive attributes that are important to farmers and their influence on the price farmers are willing to pay for seed of varieties that embody those attributes. A survey of 325 randomly selected farmers was conducted in Iganga and Masindi districts in Uganda to identify productive and consumptive attributes they preferred when purchasing seed. Results showed that maize farmers were willing to pay more for seed of short-medium height, short-medium maturity period, and high yielding maize varieties. However, the price farmers were willing to pay for maize seed not only depended on quality attributes, but also on seed market prices and land resource endowment. These results have important implications for policy makers to streamline production, multiplication and distribution of high quality maize seeds in Uganda.